Functionalized Porous Silica Microspheres as Scavengers in Parallel Synthesis - Thompson, L.A.; Combs, A.P.; Trainor, G.L.; Wang, Q.; Langlois, T.J.; Kirkland, J.J. (Combinatorial Chemistry & High Throughput Screening, 2000)
The use of solid scavengers in parallel solution-phase organic synthesis is an effective method for work-up and purification. Functionalized macroreticular or gel-form polystyrene particles are generally used for scavenging applications, how ever these materials have some limitations. We have developed new scavenging reagents based on ultrapure silica microspheres displaying a variety of functional groups useful for sequestering impurities from reaction products. These materials are easy to handle, have excellent mass-transfer properties, and are efficient scavengers in both polar and nonpolar organic solvents. The properties of these materials were tailored specifically to fit the needs of a medicinal chemist employing parallel synthesis techniques in current commercial equipment. Results are presented from head-to-head comparisons with conventional scavengers in tests designed to demonstrate the versatility of these new materials.
Keywords: Scavengers